PEMBERDAYAAN KELUARGA TERHADAP PEMANFAATAN TANAMAN OBAT KELUARGA (TOGA) PADA MASA PANDEMI COVID-19 DI DESA DERSANAN, BUTUHAN, DELANGGU, KLATEN - Puput Risti Kusumaningrum; Endang Sawitri (Anfa Mediatama, 2023)
Family medicinal plants (TOGA) are one of the people's choices for planting in their yards, with the consideration that they can be used for health. Medicinal plants can be used as drugs that are safe, do not contain chemicals, are cheap, and are easy to obtain. Utilization of these traditional medicines as an effort to maintain health, prevent disease and health care, including during a public health emergency and/or the 2019 Corona Virus Disease (COVID-19) national disaster. The methodology used is that the target family is given education regarding family medicinal plants and the benefits of TOGA as an to increase body immunity during Covid 19. The next stage is preparing empty yards ready for planting several types of TOGA plants as well as evaluating and following up community empowerment programs on the use of Family Medicinal Plants (TOGA). 8 (50%) people, enough for 6 (37.5%) people, and good for as many as 2 (12.5%) people.After being given health counseling the level of knowledge of respondents increased with less knowledge of 3 (18.75%) people, 3 (18.75%) people are enough, and 10 (62.5%) people are good. The results after counseling can be seen that the respondent's knowledge has increased and this method is considered effective in increasing the respondent's knowledge.